Associação entre polimorfismo adipoq 45 t>g do gene da adiponectina, síndrome metabólica e dieta usual em idosos de Uruguaiana/RS - (:unkn) unknown (Universidade Federal do Pampa, 2016)
The prevalence of metabolic syndrome (MS) has been growing over the years, along with an epidemic obesity in the elderly population. The current nutritional transition contributes accelerate the beginning of metabolic alterations that leads to the diagnosis of MS, and a variety of environmental factors relate to the onset of this disease. Poor eating habits which stand out excessive consumption of refined foods, high in fat and low intake of whole foods, fruits and vegetables, makes the diet low in nutritional value, possibly related to the incidence of MS. In addition to the factors mentioned MS may also be related to genetic factors, which adiponectin levels unlike other substances released by adipose tissue act as a protective factor for cardiovascular disease. Thus, the present study aims to examine a possible association between the polymorphism ADIPOQ 45 T> G, usual diet and MS in the elderly. Inflammatory and biochemical markers compared with older age groups were analyzed (age ≥60 anos) with and without the MS. Also in addition to the anthropometric measurements of weight, height and waist circumference, the ADIPOQ polymorphism 45 T> G was determined by PCR-RFLP and investigated dietary intake through food frequency questionnaire. The study included 111 elderly people, where 53.2% had not the MS and 46.8% had such decease. Our main results show that there was significant relationship between habitual consumption of milk for the group had MS (p <0.05), HDL-C levels, glucose, triglycerides and weight, height, waist circumference and diastolic blood pressure had to be altered in patients with the MS. There was an association between habitual dietary intake of white meat and vegetables with the haplotype TG and GG. We conclude that there is no association between the polymorphism ADIPOQ 45 T> G and MS in the group of elderly studied, however the relationship between habitual consumption of certain food groups and ADIPOQ indicate the need for further studies elucidate this relationship.
Polymorphism association between adipoq 45t > g of the gene adiponectin, metabolic syndrome usual and diet in elderly Uruguaiana/RS
Keywords: Síndrome metabólica; Consumo alimentar; Adiponectina; Metabolic Syndrome; Food consumption; Adiponectin